ZOOMORPHIC HANDLE CERAMICS FOUND IN MYNTOBE BURIAL GROUND (Journal of history, 2022)
Archaeological research reveals the special role of the image of animals in the worldview and religious beliefs of the nomadic tribes inhabiting the Eurasian continent. For a specific purpose, ancient inhabitants made vessels with images of animals intended for everyday life or religious rites. When researching the monuments of nomadic and sedentary tribes, vessels and cauldrons with zoomorphic handles, swords, and daggers with zoomorphic handles are increasingly found. Unfortunately, their purpose, chronology, area of distribution, and typology of zoomorphic pens have been little studied. In this article, therefore, we have presented a comparative analysis of zoomorphic handles found in monuments of the Kangly and Sarmatian tribes living in the Eurasian continent, focusing on the purpose, zoning, chronology and regional peculiarities of zoomorphic-handled ceramics. From this comparative analysis, we have identified the specific features of zoomorphic handles of the Kangly and Sarmatian tribes and the chronology of steady ceramics from burial ground number 3 in Myntobe. In addition, the article provides information about the Zhetasar, Otyrar-Karatau, and the distribution of the Kauynshy cultures